Arrhythmic burden in patients with new-onset persistent left bundle branch block after transcatheter aortic valve replacement: 2-year results of the MARE study. Issue 2 (21st October 2020) - Muntané-Carol, Guillem; Urena, Marina; Nombela-Franco, Luis; Amat-Santos, Ignacio; Kleiman, Neal; Munoz-Garcia, Antonio; Atienza, Felipe; Serra, Vicenç; Deyell, Marc W; Veiga-Fernandez, Gabriela; Masson, Jean-Bernard; Canadas-Godoy, Victoria; et al.
Abstract: Aims: We determined the incidence and type of arrhythmias at 2-year follow-up in patients with new-onset persistent left bundle branch block (LBBB) following transcatheter aortic valve replacement (TAVR). Methods and results: Multicentre prospective study including 103 consecutive patients with new-onset persistent LBBB post-TAVR (SAPIEN XT/3: 53; CoreValve/Evolut R: 50). An implantable cardiac monitor (Reveal XT, Reveal Linq) was implanted before hospital discharge and patients had continuous monitoring for up to 2 years. Arrhythmic events were adjudicated in a central core lab. 1836 new arrhythmic events (tachyarrhythmias: 1655 and bradyarrhythmias: 181) occurred at 2 years. Of these, 283 (15%) occurred beyond 1 year (tachyarrhythmias 212, bradyarrhythmias 71) in 33 (36%) patients, without differences between valve type. Most late (>1 year) arrhythmic events were asymptomatic (94%) and led to a treatment change in 17 (19%) patients. A total of 71 late bradyarrhythmias [high-degree atrioventricular block (HAVB): 3, severe bradycardia: 68] were detected in 17 (21%) patients. At 2 years, 18 (17%) patients had received a permanent pacemaker (PPM) or implantable cardiac-defibrillator. PPM implantation due to HAVB predominated in the early phase post-TAVR, with only 1 HAVB event requiring PPM implantation after 1 year. Conclusion: Patients with new-onset LBBB post-TAVR exhibited a very high burden of arrhythmic events within the 2 years post-procedure. While new tachyarrhythmic events were homogeneously distributed over time, the vast majority of new HAVB episodes leading to PPM implantation occurred early after the procedure. These results should help to guide the management of this challenging group of patients. (clinicaltrials.gov: NCT02153307)